The Integration of KKNI, SNPT, and the Integration-Interconnection Paradigm in Curriculum Development at PTKI - Faisal, Muhammad; ZA, Tabrani; Siswanto, Romi; Hayati, Hayati; Darojat, Jajat (SCAD Independent, 2021)
This study aimed to explain the development of the Islamic Religious Education (PAI) curriculum in Islamic religious higher education which refers to the Indonesian National Qualifications Framework (KKNI), the National Higher Education Standards (SNPT), and the Science Integration-Interconnection Paradigm as an orientation for scientific development at UIN Sunan Kalijaga. This research used qualitative methods with a naturalistic qualitative approach. The research took place at the Faculty of Tarbiyah and Education (FITK), UIN Sunan Kalijaga Yogyakarta with a focus on the study program of PAI. The subjects of this study consisted of the Dean, Deputy Dean, and Chair of the Study Program, lecturers, and students of PAI. The research procedure was taken in four steps: observation, in-depth interviews, and documentation. Meanwhile, the data were analyzed by using the inductive model. The findings of the study indicated as follows; first, curriculum development emphasizes the clarity of the graduate profile, learning outcomes, the PAI field of study as the scope of development, the weight of the semester credit units. Second, curriculum development accommodates professional teacher competencies with four competencies; pedagogic, personality, social and professional. Third, curriculum development in the PAI Study Program emphasizes aspects of Islamic Education with its main sources, namely the Al-Qur'an and Al-Hadith.